Multilingualisme Indonesia-Inggris-Arab pada Komunikasi Influencer Muslim dalam Podcast Escape Episode 11: Kajian Sosiolinguistik (Indonesian-English-Arabic Multilingualism in Muslim Influencers’ Communication on the “Escape” Podcast, Episode 11: A Sociol - Riska Amelia; Joko Purwanto (Universitas Sebelas Maret, 2026)
This study aims to describe the forms and functions of code-switching and code-mixing, as well as to identify the factors that trigger their occurrence on Raymond Chin’s channel in the Escape podcast, episode 11, entitled “Cara Kebal dari Djinn, Setan, dan Iblis”. The research employs a qualitative approach with a descriptive method. The object of this study consists of words, phrases, and clauses that contain code-mixing and code-switching phenomena, as expressed in conversations throughout the podcast. Data were collected using observation and note-taking techniques. Based on the results of the data analysis, it can be concluded that the phenomenon of multilingualism in Escape podcast episode 11 appears in the forms of code-switching and external code-mixing. The use of code-switching and code-mixing functions as a strategic tool in conveying islamic preaching (da’wah), expanding audience reach, enhancing emotional engagement with listeners, emphasizing key statements, and demonstrating the speaker’s deep understanding of islamic teachings. Additionally, it reflects the speaker’s social and educational background and serves as an adaptive response to situational demands in communication. The factors contributing to the occurrence of code-switching and code-mixing include: (1) the social and religious backgrounds of both the speaker and the interlocutor; (2) the topic of discussion; (3) audience orientation; and (4) limitations in linguistic codes.Penelitian ini bertujuan mendeskripsikan bentuk, fungsi, serta faktor penyebab alih kode dan campur kode pada kanal YouTube Raymond Chin dalam podcast Escape episode 11 berjudul “Cara Kebal dari Djinn, Setan, dan Iblis”. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Objek penelitian berupa ujaran dalam bentuk kata, frasa, dan klausa yang mengandung fenomena alih kode dan campur kode dalam percakapan pada podcast. Data dikumpulkan melalui teknik simak dan catat. Hasil penelitian menunjukkan bahwa fenomena multilingualisme pada podcast tersebut berbentuk alih kode dan campur kode ekstern. Penggunaan alih kode dan campur kode berfungsi sebagai strategi penyampaian dakwah Islam, memperluas jangkauan audiens, meningkatkan keterhubungan emosional, mempertegas pernyataan, menunjukkan pemahaman mendalam terhadap Islam, menggambarkan latar belakang sosial dan agama penutur, serta menyesuaikan situasi komunikasi. Faktor penyebab terjadinya alih kode dan campur kode meliputi: (1) latar belakang sosial dan agama penutur maupun lawan tutur; (2) topik pembahasan; (3) tujuan audiens; dan (4) keterbatasan kode.